Ciri Anatomi, Morfologi Serat, dan Sifat Fisis Tiga Jenis Lesser-Used Wood Species Asal Kalimantan Utara, Indonesia - Sarah Augustina; Imam Wahyudi; I Wayan Darmawan; Jamaludin Malik (Institut Pertanian Bogor, 2020)
The purpose of this study was to analyze anatomical characteristics, fiber morphology, and several important physical properties of nyatoh (Palaquium lanceolatum), pisang putih (Sindora walichii), and sepetir (Mezzettia leptopoda) wood from North Kalimantan in order to support the proper utilization of each wood species. All parameters were analyzed using their standard procedures. Results showed that anatomical characteristics of nyatoh wood are the vessels predominantly are in radial multiples and contained tyloses, ray parenchyma is mostly uniseriate and even, while axial parenchyma is in narrow tangential line with irregularly spaced. For pisang putih wood, the vessels are exclusively solitary, ray parenchyma of two distinct sizes, while axial parenchyma are in continuous tangential bands with irregularly spaced. In case of sepetir wood, the vessel is in radial and diagonal patterns, rays tend to have two different sizes, axial parenchyma is vasicentric to aliform, and has the axial resin canals in continuous tangential bands. Average values of fiber length and fiber wall thickness are 1904 and 3.61 µm (nyatoh), 1708 and 4.51 µm (pisang putih), and 1337 and 3.39 µm (sepetir), respectively; while the mean values of specific gravity and T/R-ratio are 0.42 and 1.41 (nyatoh), 0.37 and 2.34 (pisang putih), and 0.32 and 1.40 (sepetir), respectively. Nyatoh wood is categorized as the Strength Class of III, while pisang putih and sepetir woods are categorized as the Strength Class of IV. Compared to pisang putih and sepetir woods, nyatoh wood is more potential for pulp, paper, and furniture manufacturing. Keywords: anatomical characteristics, fiber morphology, lesser-used wood species, physical properties